Application Of Appropriate Technology For Automatic Bird Pest Removal And Automatic Fish Feed In The Minapadi System In Beutong Nagan Raya District - Mahendra Mahendra; Muhammad Arif Nasution; Fitria Rahmayanti; Dini Islama (International Journal Of Community Service, 2021)
The purpose of this research-based service program is to apply the research results of the proposing team's research for community empowerment. The application of the research results was carried out on the program of application of appropriate technology for automatic fish feed and automatic bird repellent on the Minapadi jajar legowo system which is a system of planting rice with fish cultivation in one rice field area simultaneously and the jajar legowo planting system with a spacing of 25 cm . The technology used is automatic feeding and automatic bird repellent. Automatic feeding is done by using a mini water pump that has been modified with the help of a digital timer so that the feed automatically dispenses the feed at the time we specify, which is 3 times a day. The second technology is automatic bird repellent using extracts of herbal ingredients (jengkol) with the help of an automatic sprayer. This technology aims to increase the income of farmers with high productivity of rice yields and increase local fish production. The activity was carried out for 5 months in Beutong Nagan Raya District. The observed results include the feed that comes out of the automatic device as much as 15 gr/second, adjusted for the number and weight of fish. Meanwhile, the air pollution that comes out every 10 minutes is 5 units in a 25m2 plot.